Map of the heads of Kjerulf and Dickson Fiords, East Greenland, 1931 / from a photographic reconnaissance by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (American Geographical Society of New York, 1932)
Relief shown by contours and spot heights.; Upper right corner: The Geographical review, vol. XXII, No. 4, 1932, Pl. III.; Includes inset, The route of the Louise A. Boyd expedition in the region of Franz Josef and King Oscar Fiords, 1931, and relative reliability chart. Color 1:50,000